Measuring the impact of user participation in agricultural and natural resource management research - Johnson, Nancy L.; Lilja, Nina; Ashby, Jacqueline A. (Elsevier, 2003)
Persistent poverty and environmental degradation demand a constant effort to improve the effectiveness and impact of agricultural and natural resource management research. Participatory research methods have developed as a way to help researchers better target their work towards the needs and constraints of specific stakeholder groups. Participatory research may also strengthen the capacity of participants to initiate a continuous process of innovation. The capacity of farmers and other end users of technologies to innovate may be particularly important in poor, marginal environments where conditions are highly variable. This paper assesses the impact of using participatory methods in three agricultural research projects which have a natural resource management focus. Mixed methods are used to assess technological, economic, human, and social impacts and the cost implications of incorporating beneficiaries into the research process. User participation was found to influence priorities and practices within and beyond the specific projects studied. Participation led to more relevant technologies and greater economic impacts, especially when participation was early in the research process. Impacts on farmer capacity were high when farmers worked intensively with researchers over a period of time. Use of participatory methods changes research costs. When farmers took over tasks that were previously done by researchers, some of the research costs were transferred to farmers. When participatory methods were combined with conventional on-farm research, there were also start-up costs, because researchers and farmers needed to learn new research methods. However these additional one-time costs were not significant in terms of total research costs.